EFEKTIFITAS TERAPI THOUGHT STOPPING TERHADAP ANSIETAS KLIEN DENGAN HIV / AIDS DI WILAYAH KOTA SEMARANG - Eni Hidayati; Riwayati - (Universitas Muhammadiyah Semarang, 2015)
As we realize that the HIV and AIDS epidemic threatens the welfare and peace of the world community, because until now has not found a cure so that vaccine development has always been aproblem of health is very serious for the whole nation including Indonesia. Aware of the modes of transmission of HIV disease and AIDS are more stems from behavioral factors, particularly sexual behavior that are not reasonable or through a vehicle syringe, the prevention and control becomes very complicated social problems as well as complex, including identification of infected efforts are likely to show the phenomenon of mountain ice. Always needs to come together and comprehensive kesinergian in prevention and mitigation, because HIV and AIDS is a major threat to national development, for the business world, gender equality and a threat to the increase in the workforce.This epidemic can result in enormous negative impact on the economic growth of the labor force, businesses, and workers and their families. The nurse as a component of most of the health care team is an important helper clients to reduce anxiety. As a professional nursing interventions in reducing anxiety is individual therapy, family therapy, group therapy and therapy psikofarmaka.Thought stopping (cessation of mind) is one example of cognitive behavioral psychotherapy techniques that can be used to help the client to change thought processes (Tang & DeRubeis, 1999). In practice, this therapy uses various variations in helping someone who is trying and stop the unpleasant thought with full consideration. Thought Stopping therapy performed by deciding thoughts or obsessions that threaten. Clients are instructed to say